'a hole worlde of things very memorable' essays in architecture, archaeology, topography and the history of Oxford presented to Julian Munby for his 70th birthday - Henig, Martin 1942-; Ramsay, Nigel 1955- (Archaeopress Publishing, 2024)
Julian Munby has gained a reputation over half a century in many branches of archaeological and historical knowledge. His lively and warm character and sense of fun has made him many friends who also in some sense feel they are his pupils, and this collection of papers has been assembled as a tribute in honour of his 70th birthday.
Keywords: Geschichte; Architektur; Oxford; England; Aufsatzsammlung; Festschrift